Motivations, Monitoring Technologies, and Pay for Performance - Cordella, Antonio; Cordella, Tito (Elsevier, 2018)
Monitoring technologies and pay for performance (PFP) contracts are becoming popular solutions to improve public services delivery. Their track record is however mixed. To show why this may be the case, this paper develops a principal agent model where agents’ motivations vary and so the effectiveness of monitoring technologies. In such a set-up, it shows that: (i) monitoring technologies should be introduced only if agents’ motivations are poor; (ii) optimal PFP contracts are non-linear/non-monotonic in agents’ motivations and monitoring effectiveness; (iii) investments aimed at improving agents’ motivations and monitoring quality are substitutes when agents are motivated, complements otherwise; (iv) if the agents’ “type” is private information, the more and less motivated agents could be separated through a menu of PFP/non-PFP contracts, designed in a way that only the less motivated ones choose the PFP.